6b+6=40

Simple and best practice solution for 6b+6=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b+6=40 equation:


Simplifying
6b + 6 = 40

Reorder the terms:
6 + 6b = 40

Solving
6 + 6b = 40

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6b = 40 + -6

Combine like terms: 6 + -6 = 0
0 + 6b = 40 + -6
6b = 40 + -6

Combine like terms: 40 + -6 = 34
6b = 34

Divide each side by '6'.
b = 5.666666667

Simplifying
b = 5.666666667

See similar equations:

| -72-3x=-11x+24 | | 5-4[2-x]=17 | | 2(2+5b)=54 | | -5m+18=6-6(-2-6m) | | 50=3m+2 | | -42+4x=2x+18 | | 4(1+5x)=84 | | y=55x+1000 | | -r-2(5r+5)=-54 | | 3/2(4-6)= | | (-1-5)/(2-2) | | (-125)-x=253 | | -4(4+5a)+3=-93 | | 3x+5-2x+5-2x+5-x= | | 3x^2+22x-16=40 | | -11x-78=-6x+37 | | -7x+15+3x=-9(x-10) | | 1/8x^2-1/4x-1/2=0 | | -42-4x=3x+70 | | 29.94+.10x=32.99+.5x | | 18=54 | | 10=-5(-3b+7) | | -8x-158=92+2x | | 3x+1+5x+11=180 | | (-3-1)/(-4-4) | | 2q(8q-5)=7+4q | | 6x-3x-7+5x+9= | | 3sin^2(2x)+2cos(2x)-2=0 | | an=30-4n | | x+x+3+4=72 | | 2(a-6)=-28 | | -7/2-9/2 |

Equations solver categories